2019
DOI: 10.1002/jcb.29505
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BAX ubiquitin‐binding sites reveals that BAX activation is essential for its ubiquitin‐dependent degradation

Abstract: BAX is an important proapoptotic protein of the BCL‐2 family, and its stability is essential for the regulation of the mitochondrial apoptotic pathway. A previous study revealed that BAX could undergo degradation through the ubiquitin‐proteasome pathway. In this study, we identified two lysine sites, K21 and K123, that were critical ubiquitin‐binding sites in BAX. Mutation of these two sites prolonged the half‐life of BAX and also affected its proapoptotic ability. Intriguingly, we found that ABT‐737, a BCL‐2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Meanwhile, the role of Ub in the regulation of intracellular levels of various tumor suppressor proteins should be addressed in GC, as already reported for BAX [ 55 ] and p53 [ 56 ] in other cancers. In a very recent paper, Peng et al [ 55 ] showed that mutation of the two ubiquitin-binding sites in the pro-apoptotic protein BAX increased its half-life and its ability to activate the intrinsic pathway of apoptosis in HCT116 tumor cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, the role of Ub in the regulation of intracellular levels of various tumor suppressor proteins should be addressed in GC, as already reported for BAX [ 55 ] and p53 [ 56 ] in other cancers. In a very recent paper, Peng et al [ 55 ] showed that mutation of the two ubiquitin-binding sites in the pro-apoptotic protein BAX increased its half-life and its ability to activate the intrinsic pathway of apoptosis in HCT116 tumor cells.…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, the role of Ub in the regulation of intracellular levels of various tumor suppressor proteins should be addressed in GC, as already reported for BAX [ 55 ] and p53 [ 56 ] in other cancers. In a very recent paper, Peng et al [ 55 ] showed that mutation of the two ubiquitin-binding sites in the pro-apoptotic protein BAX increased its half-life and its ability to activate the intrinsic pathway of apoptosis in HCT116 tumor cells. Zhou et al [ 56 ] demonstrated that the oncoprotein MNAT1 binds to p53 leading to its ubiquitin-mediated degradation through Mouse double minute 2 homolog (MDM2), decreasing apoptosis and increasing cell growth in human colorectal cancers.…”
Section: Discussionmentioning
confidence: 93%
“…However, BAX turnover can be modulated depending on the cellular context. Evidence suggests that impaired proteasomal degradation of BAX leads to TRAIL‐induced resistance to apoptosis in malignant B cells (Liu et al, 2008; Peng et al, 2020). These insights into the interplay between the ubiquitin‐proteasome system and Bcl‐2 family proteins may lead to the identification of potential therapeutic targets and strategies for cancer therapy.…”
Section: Role Of Proteasome Degradation In Regulating Bcl‐2 Family Pr...mentioning
confidence: 99%
“…Another important pro-apoptotic protein, BAX, is regulated by the ubiquitin/proteasome pathway. BAX undergoes ubiquitin-dependent degradation mediated by E3 ligases PARKIN and IBRDC2, thus preventing initiation of MOMP to induce apoptosis [154].…”
Section: Apoptosismentioning
confidence: 99%